Performance Strategies in Three Recordings of Bach’s Invention No. 1 in C Major: A Comparative Study - Dodson, Alan (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2011)
After a brief introduction to the field of empirical performance studies and its goals and methods, recordings of the titular work by pianists Harold Bauer, Glenn Gould, and Angela Hewitt are discussed. It is suggested that these recordings demonstrate three distinct performance strategies for the piece: Bauer highlights the boundaries of each phrase and projects a teleological design within each phrase and at the level of the entire piece; Gould conveys an arch-shaped design tied to harmonic tension; and Hewitt draws attention not only to the three structural cadences (mm. 7, 15, and 22) but also to a subsidiary V-I motion at m. 11, thereby hinting that it might have structural importance. Parallels between these performance strategies and analyses by Howard Cinnamon, Steve Larson, and Roy Travis are briefly considered. The emphasis on multiplicity in this study distinguishes it from most earlier scholarship on structure and performance.